Code Switching and Code Mixing in the Teaching Process: A Case Study at Rainbow School of Joy in Medan - Nova Marya Simanjuntak (ALTSA Publisher, 2022)
The objectives of this study were to find out the types and factors of code-switching and code-mixing done by the teachers in the teaching process and to reveal why teachers switched and mixed the utterances. It was conducted using a descriptive qualitative research method. The objects of this study were Mathematics, Science and English teachers at Rainbow School of Joy in Medan. The data were collected by video recording the teachers' utterances during the learning to find out types and factors of code-switching and code-mixing and by interviewing the teachers to reveal why they switched and mixed the codes. Data were analysed by using Cohen's technique (2018). The study's findings showed the teachers' most frequent types of code-switching were inter-sentential. The total is 46 types with a percentage of 18%. The most frequent types of code mixing were insertion (word phrase). The accommodation is 49 types, with a rate of 19%. The most frequent factor of the teachers doing the code-switching and mixing was talking about a particular topic. The total is 52, with a percentage of 21%. Finally, the most frequent reason was the genre. The accommodation is 12, with a rate of 27.2%.